Dialektika Moral Etik Penafsir Otoritarianisme: Pendekatan Hermeneutika Negosiatif Khaleed Moh. Abou El-Fadl - Nur Kholik; Subiantoro Subiantoro; Muhammad Wafa' (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Man is a religious being created by God so that it becomes commonplace when God sends agama for man. But it is not an easy matter to understand God's will through His symbols. While the Prophets and Apostles were alive, humans could directly confirm the appearance of the symbol. But when the Nth breed of abian is cut off from the present era, then it raises the potential for